The psichomotricity in the sensorial-auditive special educative needs environment - William Yera-Díaz; Lismay Pérez-Rodríguez; Enrique Alonso-Pedraza (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
We hope this paper would motivate reflexion on professionals and specialists who work with special educative needs, especially those of a sensorial and auditive character, in order to find a solution for many children suffering these disorders. The study of psicomoticity in children with sensorial-auditive special educative needs, acquires a greater significance because it permits to become conscious about the reciprocal dependence of the mental children life, with the motor skills, based upon its three dimensions: cognitive, affective, and motor. By means of this research, we are looking forward to develop in children their motor potentials by sport activities. At the same time, linked with the educative environment, the active participation of school, family, and the community.